Anti‐hapten antibodies in response to skin sensitization. (11th November 2015) - Singleton, Helen; Popple, Amy; Gellatly, Nichola; Maxwell, Gavin; Williams, Jason; Friedmann, Peter S.; Kimber, Ian; Dearman, Rebecca J.
Summary: Whereas T lymphocyte (T cell) activation is the key event in the acquisition of skin sensitization and subsequent elicitation of allergic contact dermatitis, the humoral component of immune responses to organic contact allergens has received little consideration. There is evidence that, in experimental animals, topical exposure to potent contact allergens is associated with B cell activation and proliferation, and hapten‐specific antibody production. However, there is very limited evidence available for anti‐hapten antibody responses being induced following topical exposure of humans to contact allergens. Nevertheless, it is important to appreciate that there are almost no negative studies in which evidence for antibody production as the result of skin sensitization has been sought and not found. That is, there is absence of evidence rather than evidence of absence. Furthermore, exposure to chemical respiratory allergens, in which the skin has been implicated as a potential route of sensitization, results in anti‐hapten antibody responses. It is proposed that skin sensitization to contact allergens will normally be accompanied by antibody production. The phenomenon is worthy of investigation, as anti‐hapten antibodies could potentially influence and/or regulate the induction of skin sensitization. Moreover, such antibodies may provide an informative correlate of the extent to which sensitization has been acquired.